The influence of ecophysiological factors on growth, aflR gene expression and aflatoxin B1 production by a type strain of Aspergillus flavus. (15th September 2017) - Bernáldez, Victoria; Córdoba, Juan J.; Magan, Naresh; Peromingo, Belén; Rodríguez, Alicia
Abstract: Maize is prone to infection by Aspergillus flavus, which can contaminate the product with aflatoxins. The objective of this study was to examine the impact that interactions between water activity (aw ) and temperature may have on growth, the expression of a biosynthetic regulatory gene ( aflR ) and aflatoxin B1 (AFB1 ) production by a strain of A. flavus on a maize-based medium. Results showed that there were some differences between lag phases and growth rates of A. flavus . The optimum growth rate for A. flavus was at 30 °C and 0.99 aw . No growth occurred at 0.90 aw and 20 °C. Both temperature and aw had an influence on the relative aflR gene expression and AFB1 production by A. flavus ; however, the results for AFB1 production were not consistent with the effects on gene expression or growth. These findings provide data that are useful to better understand the conditions which represent higher risks from AFB1 production. However, the aflR expression was not a good indicator of AFB1 production alone. Thus, further molecular studies of other AF-related genes should be done. These results are discussed in the context of harvesting and storage of maize and the prevailing environmental conditions to minimise AFB1 contamination. Highlights: Post-harvest conditions of maize affect growth and AFB1 production by A. flavus . High temperatures (≥25 °C) and aw (≥0.95) strengthen AFB1 by A. flavus in maize. The aflR gene expression is not consistent with AFB1 of A. flavus in maize-based media. The drying speed and storage temperature of maize must be controlled to avoid AFB1 .